2019
DOI: 10.1016/j.cnsns.2019.104896
|View full text |Cite
|
Sign up to set email alerts
|

Discrete resonant Rossby/drift wave triads: Explicit parameterisations and a fast direct numerical search algorithm

Abstract: We report results on the explicit parameterisation of discrete Rossby-wave resonant triads of the Charney-Hasegawa-Mima equation in the small-scale limit (i.e. large Rossby deformation radius), following up from our previous solution in terms of elliptic curves (Bustamante and Hayat, 2013). We find an explicit parameterisation of the discrete resonant wavevectors in terms of two rational variables. We show that these new variables are restricted to a bounded region and find this region explicitly. We argue tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A Rossby wave solution is given explicitly by the parameterized function , where is an arbitrary constant, is the so-called dispersion relation, and is called the wave vector. For simplicity, we take and in what follows [ 32 , 33 ].…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…A Rossby wave solution is given explicitly by the parameterized function , where is an arbitrary constant, is the so-called dispersion relation, and is called the wave vector. For simplicity, we take and in what follows [ 32 , 33 ].…”
Section: Preliminariesmentioning
confidence: 99%
“…New parameterization: In [ 40 ], Kopp parameterized the resonant triads and in terms of parameters u and t it follows by [ 40 ] (Equation (1.22)) that: In 2019, Hayat et al [ 33 ] found a new parameterisation of and D in terms of auxiliary parameters and hence and are given by: …”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations